Pengaruh Kepribadian, Kelas Sosial, dan Budaya Pengusaha terhadap Strategi Pemasaran dan Keputusan Menjadi Nasabah Bank Syariah Mandiri di Sumatera Barat - Pasrizal, Himyar; Salim, Ubud; nimran, Umar (Universitas Brawijaya, Indonesia, 2012)
This study aims to develop and test the consistency of variables relationship that influences Bank Syariah Mandiri's (BSM) consumer' behavior. According to theories and review of previous studies, customers' internal and external factors and marketing strategies of Islamic banks which are considered or perceived by the customers influence their decision to become customers of the Islamic banks. However, previous researches have shown inconsistent results in which some claimed that religion factor became themain reason to deal with Islamic banks, while others said it was not. This study specifically analyzes the variables of personality, social class, culture, and marketing strategies in influencing decision to become BSM's customers. The population in this study is all clients or customers of BSM in West Sumatra in 2010. The research sample is 383 customers. The sampling was done by using purposive sampling and the analysis was conducted by using Structural Equation Modeling (SEM) as an analysis tool. The results show that: (1) Traits of the customers' personality do not impose power over their decisions to become customers of BSM. (2) The higher position of customers' social class can encourage their decision to become customers of BSM. (3) The stronger the customers' culture, the stronger their decision to become customers of BSM. (4)The better the marketing strategies of Islamic banks are considered and perceived by customers, the more encouraged and stronger their decisions to become customers of BSM.